Pengaruh perendaman dengan jus umbi bit merah (beta vulgaris l.) terhadap perubahan warna restorasi resin komposit nanofiller - Widyastuti, Wiena; Agnes (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: To achieve an aesthetic restoration, it is necessary to choose the right technique and material. Nanofiller composite resin is an option in aesthetic restoration because it has high aesthetic qualities, mechanical properties, and wear resistance. The presence of discoloration in composite resin restorations is undesirable because it interferes with the aesthetic value and appearance. Changes in the color of the restoration caused by extrinsic factors are influenced by color pigments and acidic pH contained in the food and beverages consumed, for example, red beetroot. Objective: This study aims to determine the effect of consumption of red beetroot on the color change of nanofiller composite resin, by immersing it in red beetroot juice. Methods: The object of this research is a cylindrical nanofiller composite resin with a diameter of 10 mm and a thickness of 2 mm. The research was conducted by immersing the nanofiller composite resin in red beetroot juice and aquadest. The study was divided into 2 groups, the control group and the test group, which were placed in an incubator with a temperature of 37oC for 24 hours. In the treatment group, samples were immersed in red beetroot juice for 4 hours for 7 days, followed by immersion in distilled water. In the control group, samples were immersed in distilled water for 24 hours. The color parameters of the research subjects were measured using Vita Easyshade V, before and after treatment for 7 days. After the normality test, the acquired data was statistically tested using Mann-Whitney test and T-test (Independent). Results: The results of this study showed a significant color change (p<0.05). Conclusion: There is an effect of soaking with red beetroot juice on the color change of the nanofiller composite resin.